2020
DOI: 10.1111/dth.14639
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of onychotillomania and onychophagia in graduate students

Abstract: Dear Editor, Onychotillomania and onychophagia are body-focused repetitive behaviors (BFRB) involving the nail unit. Estimated prevalence is 23% to 47%, peaking in adolescence and decreasing with age, 1 and may be higher in populations experiencing stress, including students. 2 Our objectives were to assess prevalence, psychiatric co-morbidities, and treatment of onychophagia and onychotillomania in medical and graduate students. An anonymous, multiple-choice survey was emailed to medical and graduate students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It would be expected for methamphetamine-induced excoriations to be present more diffusely on the trunk, face, and extremities. Dermatillomania is a nonspecific term for excoriation disorder (or chronic skin-picking), which also manifests on other body parts [ 18 ]. Although it can also be localized to the area surrounding the nails, our patient’s excessive fixation on the nail itself meant that the trauma to the periungual skin was likely an extension of the onychotillomania.…”
Section: Discussionmentioning
confidence: 99%
“…It would be expected for methamphetamine-induced excoriations to be present more diffusely on the trunk, face, and extremities. Dermatillomania is a nonspecific term for excoriation disorder (or chronic skin-picking), which also manifests on other body parts [ 18 ]. Although it can also be localized to the area surrounding the nails, our patient’s excessive fixation on the nail itself meant that the trauma to the periungual skin was likely an extension of the onychotillomania.…”
Section: Discussionmentioning
confidence: 99%
“…Onychotillomania is less common and almost exclusively seen in adults (Haneke, 2013). Previous studies have shown that onychotillomania presented in 0,9% of participants, and more common in students aged from 18 to 45 years, 46.4% respectively (Wu, 2021). The factors influencing the data could be different, including responders age, diagnostic method, and possible patient openness.…”
Section: Prevalencementioning
confidence: 94%
“…Exact prevalence and incidence is not known, but onychophagia and onychotillomania are probably underrecognized. A recent study (Wu, Lin, & Cooley, 2021;Houghtona, Alexandera, Bauera, & Woodsa, 2018) found significant increase in incidence of self-destructive behavior.…”
Section: Introductionmentioning
confidence: 93%